Evaluation of the Implementation of Government Accounting Standards Statement Number 02 Concerning Budget Realization Reports (Case Study at the Regional Revenue Service of Biak Numfor Regency) - MBAUBEDARI, Aryandum; MORASA, Jenny; MARADESA, Djeini (Journal of Governance, Taxation and Auditing, 2025)
This research aims to evaluate the implementation of the Budget Realization Report Statement at the Regional Revenue Service of Biak Numfor Regency for the period 2020 and 2021 based on Regulation No. 71 of 2010 concerning Government Accounting Standards. This study employs a qualitative method with a descriptive approach, which aims to describe the actual condition of the research object at the time the research was conducted directly. Data collection techniques use interviews and documentation. The results of the research show that overall, the Regional Revenue Service of Biak Numfor Regency has implemented LRA Reporting in accordance with PSAP No. 02 except for transfer accounts, financing and Budget Financing Excess (SILPA) and/or Budget Financing Excess Difference (SIKPA) caused by these accounts. It is not a component of the main duties and functions of the Regional Revenue Service of Biak Numfor Regency. This demonstrates adherence to government accounting standards and supports the realization of transparency and accountability in regional financial management. Nevertheless, this study opens opportunities for further research on the effectiveness of accrual-based SAP implementation in other regions, particularly in evaluating the quality of implementation and the challenges faced by local governments in maintaining consistency in financial reporting.